Influence of ion viscosity on the distribution of parameters in the sheath at the boundary of a stationary weakly ionized strongly nonisothermal plasma - Leleko, Ya.F. (Problems of Atomic Science and Technology, 2023)
A stationary weakly ionized highly nonisothermal plasma is considered in the hydrodynamic approximation. Taking into account the effects of ionization, recharging, and a self-consistent field, the effect of ion viscosity on the distribution of plasma discharge parameters in the sheath was investigated. Distributions of hydrodynamicion velocity and ion density, electron density, and self-consistent field potential in the sheath were obtained. Розглянуто стаціонарну слабко іонізовану сильно неізотермічну плазму в гідродинамічному наближенні. З урахуванням ефектів іонізації, перезарядки самоузгодженого поля досліджено вплив в’язкості іонів на розподіл параметрів плазмового розряду в перехідному шарі. Отримано розподіли гідродинамічних швидкості та густини іонів, густини електронів і потенціалу самоузгодженого поля у цьому шарі.